The Diffusion of Innovation on the Villageâ€™s Population Administration Service (Pesta Dansa) in Sukoharjo Village, Sukoharjo District, Wonosobo Regency - Fajar, Ridwan Kurnia; Sakir, Sakir (Universitas Muhammadiyah Ponorogo, 2022)
This research aims to review the diffusion of innovation on â€œPesta Dansaâ€ (Pelayanan Administrasi Kependudukan di Desa) or the Villageâ€™s Population Administration Service in Sukoharjo Village, Sukoharjo District, Wonosobo Regency. The involved parties in this research are including the Population and Civil Registration Service of Wonosobo Regency, the Sukoharjo Villageâ€™s Government, as well as the community receiving the â€œPesta Dansaâ€ innovation service. This research uses a mixed method combined with a case study approach. The results show that the diffusion of â€œPesta Dansaâ€ innovation in Sukoharjo Village has been running well. This is evidenced by the successful implementation of â€œPesta Dansaâ€ innovation in Sukoharjo Village, by referring to 5 indicators proposed by Roger in the diffusion of innovation theory, including; 1) Knowledge, theâ€œPesta Dansaâ€ innovation has the suitability of benefits to the problem of population administration services in Sukoharjo Village; 2) Persuasion, the success of Sukoharjo Villageâ€™s government in introducing the â€œPesta Dansaâ€ innovation to the community; 3) Decision, the acceptances and supports from the Sukoharjo Villageâ€™s government as well as the community towards the implementation of â€œPesta Dansaâ€Â innovation; 4) Implementation, the success of Sukoharjo Villageâ€™s government in applying the â€œPesta Dansaâ€ innovation to the community; 5) Confirmation, the communityâ€™s assessment and evaluation survey results regarding the implementation of â€œPesta Dansaâ€ innovation by the Sukoharjo Villageâ€™s government.